International monetary policy spillovers in an asymmetric world monetary system - The United States and China - Kristina Spantig (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2012)
The paper scrutinizes the spillover effects of expansionary monetary policies of a center economy to the macroeconomic policies of periphery countries, dependent on the exchange rate regime. In particular the impact of the US quantitative easing on the Chinese economy is analysed. The results suggest that the exchange rate regime plays a minor role in insulating the economies at the periphery of the world monetary system from monetary policy shocks in the center. The only exception is capital controls which enable the periphery countries, in particular China, to maintain a certain degree of monetary independence in the short run. In the long run a closer Chinese-European policy coordination is argued to create a counterbalance to the predominance of the US dollar in the currently asymmetric world monetary system. This would provide an incentive to the US to phase out undue monetary expansion.
urn:nbn:de:gbv:27-20131119-151817-4
Keywords: E31; E42; E52; E61; 330; monetary policy; excess liquidity; spillovers; US; China; Geldpolitik; Spillover-Effekt; Liquidität; Internationales Währungssystem; USA; China